2017
DOI: 10.1242/jeb.163303
|View full text |Cite
|
Sign up to set email alerts
|

The nervous system does not compensate for an acute change in the balance of passive force between synergist muscles

Abstract: It is unclear how muscle activation strategies adapt to differential acute changes in the biomechanical characteristics between synergist muscles. This issue is fundamental to understanding the control of almost every joint in the body. The aim of this human experiment was to determine whether the relative activation of the heads of the triceps surae [gastrocnemius medialis (GM), gastrocnemius lateralis (GL) and soleus (SOL)] compensates for differential changes in passive force between these muscles. Twentyfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…2A). Large individual differences in EMG amplitude ratio already have been reported for knee extensors (14) and ankle plantar flexors (21). For example, Hug et al (14) reported a VL/VM activation ratio ranging from 33.6 to 74.7% during an isometric knee extension task performed at 20% of MVC, with an almost equal number of participants demonstrating either greater VL activation or greater VM activation.…”
Section: Individual Muscle Activation Strategiesmentioning
confidence: 95%
“…2A). Large individual differences in EMG amplitude ratio already have been reported for knee extensors (14) and ankle plantar flexors (21). For example, Hug et al (14) reported a VL/VM activation ratio ranging from 33.6 to 74.7% during an isometric knee extension task performed at 20% of MVC, with an almost equal number of participants demonstrating either greater VL activation or greater VM activation.…”
Section: Individual Muscle Activation Strategiesmentioning
confidence: 95%
“…Interestingly, previous studies examining the muscle shear modulus during contraction have reported a nonlinear response with contraction intensity (Bouillard et al 2012), and a heterogeneous shear modulus between synergistic muscles (Bouillard et al 2012;Lacourpaille et al 2017). The nonlinear response opposes what is expected with the myoelectric response (i.e., linear response) during an isometric contraction at a given joint angle (Kellis and Katis 2008;Campy et al 2009).…”
Section: Introductionmentioning
confidence: 91%
“…This has also recently been observed in vivo using SWE during a passive condition (i.e., no muscle contraction) (Umegaki et al 2015a, b;Le Sant et al 2015;Miyamoto et al 2017); while it has been shown that ST stiffness was the lowest among the hamstring muscles. However, measurements under passive conditions are unlikely to reflect the stiffness response during contraction (Shinohara et al 2010;Lacourpaille et al 2017). Therefore, the stiffness of each hamstring muscle during contraction remains to be examined in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…1B). As previous studies have shown differential changes in neural drive between GL and GM/SOL during constrained isometric plantarflexions (Lacourpaille et al, 2017;Hug et al, 2021a), we hypothesized that two main sources of common inputs may drive the triceps surae muscles during plantarflexion. Thus, we simulated 100 motor neurons receiving common and independent synaptic inputs using the model developed by Elias and Kohn (2013), with two compartments for the soma and the dendritic tree.…”
Section: Part 1: Simulationsmentioning
confidence: 99%